2019
DOI: 10.3389/fpsyg.2019.00858
|View full text |Cite
|
Sign up to set email alerts
|

Congruency Encoding Effects on Recognition Memory: A Stage-Specific Account of Desirable Difficulty

Abstract: Recent research suggests that selectively attending to relevant stimuli while having to ignore or resist conflicting stimuli can lead to improvements in learning. While mostly discussed within a broader “desirable difficulty” framework in the memory and education literatures, some recent work has focused on more mechanistic questions of how processing conflict (e.g., from incongruent primes) might elicit increased attention and control, producing enhanced incidental encoding of high-conflict stimuli. This enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(99 reference statements)
2
10
0
Order By: Relevance
“…Previous research showed that the effect of response-category conflict emerged despite using different tasks at study, namely word reading in Rosner, D'Angelo, et al (2015), a face-word Stroop task in Krebs et al (2015), semantic priming in Ptok et al (2019) and word categorization in our study. This indicates that the effect of response-category conflict is quite robust across different paradigms.…”
Section: Response-category Conflictsupporting
confidence: 41%
See 1 more Smart Citation
“…Previous research showed that the effect of response-category conflict emerged despite using different tasks at study, namely word reading in Rosner, D'Angelo, et al (2015), a face-word Stroop task in Krebs et al (2015), semantic priming in Ptok et al (2019) and word categorization in our study. This indicates that the effect of response-category conflict is quite robust across different paradigms.…”
Section: Response-category Conflictsupporting
confidence: 41%
“…For example, the mixed presentation of congruent and incongruent trials resulted in a strategy which was viable for both conditions, hence no effect on memory emerged. In a recent study, Ptok, Thomson, Humphreys, and Watter (2019) investigated a response-category conflict in a semantic priming paradigm. Similar to our study, they found a beneficial effect on memory only under specific circumstances.…”
Section: Response-category Conflictmentioning
confidence: 99%
“…Lastly, and perhaps more interestingly, manipulations of congruency at the item level, which undoubtedly imply learning about specific items, still did not affect our participants' ability to recognize old items in any differential way. The absence of statistically significant differences when using null hypothesis significance testing, together with the use of Bayesian statistics to assess the likelihood of a null result in the presence of a true effect, greatly supports the claim that conflict at encoding does not directly lead to a better encoding of the target information (see Muhmenthaler & Meier, 2019;Ortiz-Tudela et al, 2016;Ortiz-Tudela et al, 2018;Ptok, Thomson, Humphreys, & Watter, 2019, for similar findings). Several accounts of cognitive control depict LWPCE and CSE as a reinstatement of a previous response set linked with specific stimulus features.…”
mentioning
confidence: 62%
“…A somewhat related literature has assessed incidental memory for the actual task stimuli in Stroop-type paradigms, with rather mixed results. Here, some studies have shown that participants can better remember incidentally encoded incongruent relative to congruent target stimuli, suggesting that conflict can enhance memory (Davis et al, 2019;Krebs et al, 2015;Ptok et al, 2019;Ptok et al, 2020;, while others have found null results or worse memory for incongruent targets (Jiménez et al, 2020;Ortiz-Tudela et al, 2017). Moreover, there is debate on whether putative memory enhancements may be driven by response conflict or semantic conflict (Muhmenthaler & Meier, 2019;Ptok et al, 2019;Ptok et al, 2020).…”
Section: Subsequent Memory Effectsmentioning
confidence: 98%
“…Moreover, there is debate on whether putative memory enhancements may be driven by response conflict or semantic conflict (Muhmenthaler & Meier, 2019;Ptok et al, 2019Ptok et al, , 2020.…”
Section: Subsequent Memory Effectsmentioning
confidence: 99%